Evaluation of Early Transcutaneous Bilirubinometry to Predict Subsequent Hyperbilirubinemia in Neonates Admitted to a Well-Baby Nursery - Jackson, Gregory L.; Saumur, Meghan; Chandwani, Vinita; Engle, William D. (American Journal of Perinatology, 2015)
Objective The aim of this study is to determine whether a transcutaneous bilirubin (TcB) value obtained within 6 hours of birth (early transcutaneous bilirubin [ETcB]) either alone, or used to calculate an early rate of rise (E-ROR) in TcB, will identify those neonates who are at a higher risk for subsequent jaundice.Study Design ETcB values were obtained from a convenience sample of neonates admitted to the newborn nursery. E-ROR was calculated as the average hourly increase between ETcB and subsequent TcB obtained at 18 to 36 hours of age. TcB percentile values at various ages were obtained from a previously published and cross-validated nomogram. The predictive values relating ETcB, E-ROR, and TcB at 18 to 36 hours of age to TcB at 42 to 66 hours of age were determined, and receiver-operator characteristic curves were compared.Results A total of 516 late preterm and term neonates were studied. ETcB was higher (p = 0.003) in those neonates who subsequently received phototherapy (n = 15), and negative predictive value was always ≥ 0.96; positive predictive value (PPV) ranged from 0.04 to 0.06. Compared with ETcB, TcB at 18 to 36 hours was more likely to predict significant jaundice at 42 to 66 hours of age.Conclusion Given the observed low PPV, ETcB is not useful in identifying infants who develop subsequent hyperbilirubinemia. However, it may be helpful in identifying those neonates at a low risk of subsequent hyperbilirubinemia.
Keywords: jaundice; neonate; transcutaneous bilirubinometry; hyperbilirubinemia